Discrepancies in child and parent reporting of concussion symptoms. (12th May 2021) - Liu, Ruikang; Hicks, Steven D.
ABSTRACT: Objective : To assess discrepancies between child and parent symptom reports following concussion. Methods : Prospective cohort study involving 61 patients, age 7–21 years, diagnosed with a concussion within the previous 14 days. Children/parents completed the Child SCAT-3 symptom inventory at enrollment and 4 weeks post-injury. A within-subjects t -test was used to compare differences in child/parent response for each of 20 individual symptoms, 4 symptom domains, and total symptom severity. Pearson correlations were used to measure agreement between child/parent responses. A repeated measures analysis of variance assessed the effect of time on child/parent symptom discrepancy. Results : At enrollment, children reported higher symptom severity for 'distracted easily' (adj. p = .015) and 'confused' (adj. p = .015). There was moderate-to-high (r > 0.3) agreement between children and parents for more individual symptoms at enrollment (18/20) than at 4 weeks post-injury (14/20). Age had no effect ( p > .05) on the discrepancy between child/parent reports. Conclusions : Although there was moderate-to-strong agreement between child/parent reports of concussion symptoms, discrepancies in individual cognitive symptom reports exist, in both children and adolescents. Therefore, collection of parent scales may provide useful information when tracking cognitive symptoms in adolescent patients, who may under-report or under-recognize cognitive deficits.